3D-PLA-experimental set up to display the electrical background of the so-called geometric factor of electrokinetic cells. Issue 26 (29th June 2021) - Romero-Guzmán, Daniel; Gallardo-Moreno, Amparo M.; González-Martín, M. Luisa
Abstract : The so-called L / S geometrical factor has an electrical background. This can lead to changes in zeta potential of the material up to 80% working with different configurations of the electrokinetic cell. Abstract : The so-called geometric factor defined in electrokinetic cells, L / S ( L being the length and S the cross-section of the channel), is relevant for providing the surface interaction electrical potential (zeta potential, ζ ) of large surfaces, such as those used in the design of biomedical devices or water purification systems. Conversely, recent studies demonstrate that this factor is also employed to determine geometrical parameters, such as porosity in membrane-like systems. This factor, which has been attributed exclusively a geometrical character, can also be obtained from the electrical conductivity and resistance of the electrokinetic channel. In this work, we assess whether these two ways of obtaining the L / S factor are equivalent and how possible deviations can affect the value of the zeta potential. For this purpose, we work with channels of different geometries obtained by 3D printing using PLA (polylactic acid) as a polymer employed in biomedical applications. The discrepancies between the L / S factor obtained by electrical and purely geometrical measurements increase as the geometrical L / S factor becomes larger, reaching differences close to 80%. The results show that the so-called geometrical L / S factor also has an important electrical contribution and would be better denoted as electrogeometric factor. The differences found between the L / S factors are also propagated to the calculation of ζ but an optimum conductivity zone (from about 10 to 40 mS m −1 ) can be defined to obtain the zeta potential by selecting any of the L / S factors obtained from electrokinetic measurements. The results of this work should be taken into account in those investigations that use the L / S factor to obtain the geometry-porosity of permeable materials.